Aktualʹnye problemy obuchenii͡a russkomu i͡azyku. Current issues of the Russian langauge teaching. - Sokolova, Anastasia (Sborník prací Pedagogické fakulty Masarykovy univerzity v Brně ;, 2016)
Collection of papers "Current issues of the Russian language teaching XII" is devoted to issues of methodology of teaching Russian as a foreign language, to issues of linguistics and literary science. It is a result of the international scientific conference of the same name which took place on 9-11 May 2016 in Brno (Czech Republic)